The judicial appointment process in Kenya and its implications for judicial independence - Sibalukhulu, Nompumelelo (University of Pretoria, 2014)
In order to complement existing empirical research on democratic consolidation in Kenya and the role of the judiciary in particular, this mini-‐dissertation analyses the relationship between judicial appointment processes and judicial independence in Kenya. The escalation of corruption, centralisation and abuse of power by the executive, the lack of government accountability and post-‐election conflict of 2007 is linked to the dominance of the executive and corresponding subservience of the judiciary. Historically, judicial appointments have been the ambit of the President. The powers given to the President to appoint and remove judges have resulted in judicial appointments premised on allegiance to the executive rather than on upholding justice and the Bill of Rights. To rectify this deficiency, the 2010 Constitution has introduced a merit based system of judicial appointments that meets international standards on judicial independence. The new process requires the President to limit his appointments to the recommendations of a Judicial Service Commission whose responsibility it is to shortlist candidates through a transparent public process. An analysis of the selection of Kenya’s sitting Chief Justice and Deputy Chief Justice demonstrates that the reformed judicial appointment process has delegitimised the executive’s dominance over the judiciary and by so doing has placed Kenya on the road restoring judicial independence. === Dissertation (MPhil)--University of Pretoria, 2012. === gm2014 === Centre for Human Rights === unrestricted